97.7k views
1 vote
Hey answer the attachment please i really need it thank you very much!

Hey answer the attachment please i really need it thank you very much!-example-1

2 Answers

1 vote

Answer:

a) 3n - 1

b) 2n + 7

Explanation:

a) a = 2

d = 5 - 2 = 3

An = 2 + 3(n - 1)

= 2 + 3n - 3

= 3n - 1

b) a = 9

d = 11 - 9 = 2

An = 9 + 2(n - 1)

9 + 2n - 2

2n + 7

User Chaos Manor
by
5.4k points
4 votes

Answer:

a)
a_n=3n-1

b)
a_n=2n+7

Explanation:

This is just an arithmetic sequence. The generic form of an arithmetic sequence is:
a_n=a_1+d(n-1) , where
a_1 is the first term of the sequence and d is the common difference.

a) Here, we can see that the common difference is 3 (because 5 - 2 = 3, 8 - 5 = 3, etc). So, d = 3. Also, the first term is 2, so a_1 = 2. Now, we can just write our expression:


a_n=2+3(n-1)


a_n=3n-1

b) Here, the common difference is 2 (since 11 - 9 = 2, 13 - 11 = 2, etc). So, d = 2. Also, the first term is 9, so a_1 = 9. Now our expression is:


a_n=9+2(n-1)


a_n=2n+7

Hope this helps!

User Nauman Malik
by
6.1k points